2019
DOI: 10.1038/s41556-019-0406-2
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome folding intermediate at the condensin-to-cohesin transition during telophase

Abstract: A chromosome folding intermediate at the condensin-to-cohesin transition during telophase.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
188
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(227 citation statements)
references
References 68 publications
30
188
3
Order By: Relevance
“…The different dynamic properties of loop formation we observe in interphase and metaphase suggest that different molecular activities may be responsible for loop formation during the cell cycle 15,29 . Recent work has suggested that cohesin could extrude loops in interphase, though this activity has not been directly visualized in cellular contexts [30][31][32] .…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…The different dynamic properties of loop formation we observe in interphase and metaphase suggest that different molecular activities may be responsible for loop formation during the cell cycle 15,29 . Recent work has suggested that cohesin could extrude loops in interphase, though this activity has not been directly visualized in cellular contexts [30][31][32] .…”
mentioning
confidence: 78%
“…In interphase, chromatin is organized into compartments and topological-associating domains (TADs) that are cell-type specific 4-7 , whereas in metaphase, chromosomes undergo large-scale compaction, leading to the loss of specific boundaries and the shutdown of transcription [8][9][10][11][12] . Loop extrusion by structural maintenance of chromosomes complexes (SMCs) has been proposed as a mechanism to organize chromatin in interphase and metaphase [13][14][15][16][17][18][19] . However, the requirements for chromatin organization in these cell phases are very different, and it is unknown whether loop extrusion dynamics and the complexes that extrude them also differ.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To measure more precisely the spatial distributions of cohesin loops, we computed the loop spectrum on pairs of cohesin peaks (Fig 2d) using Hi-C data of Hela synchronized cells released from mitosis into G1 [17]. At the beginning of the kinetics, the spectrum is flat with no significant loop scores.…”
Section: Detection and Quantification In Mammalsmentioning
confidence: 99%
“…C-Walks generated from Hi-C data C-walks were computationally generated from non-synchronous HeLa S3 pairwise Hi-C data. The Hi-C experiment was performed as described 48,49 . For each computationally generated walk, one 1 kb bin from chromosome 4 was selected at random.…”
Section: Virtually Digest Reads At Gatc Sitesmentioning
confidence: 99%